Maternal IgG in hemolytic disease of the fetus and newborn-ABO incompatibility - Wibowo, Heri; Nurrahmah, Sheila; Gantini, Ria Syafitri Evi (Medical Journal of Indonesia, 2024)
BACKGROUND Hemolytic disease of the fetus and newborn (HDFN) is a type of anemia in the fetus or newborn, characterized by anemia, jaundice, hyperbilirubinemia, and brain damage. IgG is the only antibody that can cross the placenta. The IgG subtypes have a different ability to destroy red blood cells (RBCs). IgG1 and IgG3 can bind to Fc-phagocyte cell receptors and cause hemolysis, while IgG3 has more ability than IgG1. This study aimed to identify the antibody IgG subtype contributing to clinical manifestation differences in HDFN. METHODS This study used blood and umbilical cord blood samples from 30 pairs of mother-baby. The samples were grouped into control (not jaundice/normal bilirubin levels) and jaundice/hyperbilirubinemia groups. A self-developed IgG subtype enzyme-linked immunosorbent assay protocol was performed on maternal samples, resulting in optical density. Statistical analysis was performed using SPSS software version 23. RESULTS Blood type was associated with total bilirubin expression (p = 0.005). IgG1 anti-A, IgG3 anti-A, IgG4 anti-A, IgG1 anti-B, IgG3 anti-B, and IgG4 anti-B significantly affected hyperbilirubinemia in newborns (p = 0.041, 0.013, 0.017, 0.028, 0.001, and 0.007, respectively). CONCLUSIONS IgG1 and IgG3 were more significant in causing clinical problems. IgG4 suppressed IgG activation, resulting in no destruction of the infant’s RBCs.